Arbeit. Philosophische, juristische und kulturwissenschaftliche Studien - Baer, Josette (Schwabe interdisziplinär, 2014)
We may consider labour as boon or bane ‒ man's existence is not conceivable without labour. The expulsion from the Garden of Eden can be understood as a punishment for the consumption of the forbidden fruit from the tree of knowledge, but it can likewise be interpreted as the perfection of God's creation. Hence only beyond Eden, God's creature becomes man. He or she becomes human by cultivat-ing the earth, by working. Labour is not only a necessary evil in order to secure existence, nor does it serve as a means for self-preservation, but also for self-fulfillment. Labour is the epitome of the ability of self-being and thus of man's liberty.